ANALISIS DAN PERANCANGAN SISTEM INFORMASI MANAJEMEN ASET PADA DINAS PEMBERDAYAAN MASYARAKAT, PEREMPUAN DAN PERLINDUNGAN ANAK KOTA JAMBI - Suwandi, Deby Fransiska; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2019)
Dinas Pemberdayaan Masyarakat, Perempuan dan Perlindungan Anak Kota Jambi has the main task of helping to coordinate the regional secretary in organizing the formulation, stipulation, coordination, and control of the implementation of tasks as well as government programs and activities. Asset management in Jambi City DPMPPA is done manually and uses Microsoft Office Excel so that the performance of the asset management system is still not optimal. One way for management to be more optimal is to use information systems. This asset management research is carried out at the stage of asset planning, asset acquisition, asset acceptance, and asset placement. This study produced a prototype system that describes the functional planning, procurement, receipt and placement of assets in the Jambi City DPMPPA. The method used is an object-oriented approach using UML (Unified Modeling Language), namely use case diagrams, class diagrams, and activity diagrams. This research produced a prototype that could be implemented further so as to produce an asset management information system that could be implemented in the Jambi City DPMPPA.